PENGARUH GAYA BELAJAR DAN KEGIATAN EKSTRAKURIKULER TERHADAP PERKEMBANGAN PESERTA DIDIK DI SEKOLAH DASAR DI SD NEGRI 3 TANGERANG - Rahmawati Eka Saputri; Kesya Irene Dahayu; Livia Cahya Fadillah , Siti Nurkamillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the influence of learning styles and extracurricular activities on student development atCiledug 3 Public Elementary School. This research employs a qualitative descriptive method, with data obtainedthrough direct observation and in-depth interviews with the subjects. The findings demonstrate that understandinglearning styles (visual, auditory, and kinesthetic) helps students absorb information effectively. Furthermore, extracurricular activities play a significant role in developing students' character, creativity, and social skills. These two aspects support each other in creating a learning profile that is characterized by readiness to face the challenges ofthe 21st century.